Women in portuguese advertisements and gender stereotyping - Pereira, Francisco José Costa (2021)
The aim of this study is to identify gender stereotyping in Portuguese advertisement, thus verifying if these stereotypes are conveyed to receivers, especially young people. We set out to identify which factors lead to the discrimination of women in advertisement, which roles each character take on and what type of instrumental and terminal values are conveyed in Rokeach’s perspective (1968, 1973). We set out to perceive if the person’s attitude towards advertisement had influence on his/her analysis. We wanted to know if the person’s attitude towards advertisement, especially negative attitudes due to scepticism, influenced or not their perception of discrimination against women in advertisement in comparison to men.